2017
DOI: 10.1002/em.22159
|View full text |Cite
|
Sign up to set email alerts
|

A functional SNP in the 3′‐UTR of TAP2 gene interacts with microRNA hsa‐miR‐1270 to suppress the gene expression

Abstract: The transporter associated with antigen processing 2 (TAP2) is involved in the development of multidrug resistance and the etiology of immunological diseases. In this study, we investigated whether the expression of TAP2 can be perturbed by single nucleotide polymorphisms (SNPs) located in 3′-untranslated region (3′-UTR) of the gene via interactions with microRNAs. Using a series of in silico assays, we selected the candidate microRNAs (miRNAs) with the potential to interact with functional SNPs of TAP2. The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 56 publications
0
14
1
Order By: Relevance
“…In the present study, bioinformatics analysis, RNA pull-down, and FISH experiments confirmed that Cdr1as could adsorb miR-1270 in bladder cancer. Although miR-1270 in tumors is rarely reported (Knox et al, 2018;Zhong et al, 2018), our study found that miR-1270 expression is higher in tumor tissues than in adjacent normal tissues. We also discovered that upregulated miR-1270 inhibits cell apoptosis and significantly reduces the cisplatin chemosensitivity of T24 and EJ cells.…”
Section: Discussioncontrasting
confidence: 49%
“…In the present study, bioinformatics analysis, RNA pull-down, and FISH experiments confirmed that Cdr1as could adsorb miR-1270 in bladder cancer. Although miR-1270 in tumors is rarely reported (Knox et al, 2018;Zhong et al, 2018), our study found that miR-1270 expression is higher in tumor tissues than in adjacent normal tissues. We also discovered that upregulated miR-1270 inhibits cell apoptosis and significantly reduces the cisplatin chemosensitivity of T24 and EJ cells.…”
Section: Discussioncontrasting
confidence: 49%
“…The PolymiRTS database 3.0 ( http://compbio.uthsc.edu/miRSNP ) and miRNA Target Detection ( http://www.microrna.org/microrna/getGeneForm.do ) were used to predict the candidate miRNAs which bind the selected 3′-UTR sequences. LD analysis was analyzed based on the 1000 Genomes data for the CEU population using the SNP Annotation and Proxy (SNAP) tool ( http://www.broadinstitute.org/mpg/snap ) 31 . An online software, the RNAhybrid program ( http://bibiserv.techfak.uni-bielefeld.de/rnahybrid ), was employed to calculate the minimum free energy (MFE) of hybridization between miRNAs and their potential target sequences with MFE < −20 kcal/mol as the threshold were selected according previous study 29 , 31 .…”
Section: Methodsmentioning
confidence: 99%
“…Our results suggest for the first time that individuals with T allele of FAM20B (rs3766626) appear to have a low risk of mesiodens, which was located in the 3′ untranslated region (3′ UTR) of corresponding gene. Although it isn’t translated into protein, previous and recent studies showed that variant in 3′ UTR region could impact the expression of mRNA [33, 34].…”
Section: Discussionmentioning
confidence: 99%